Representation of Women in a Room of One's Own by Virginia Woolf: Exploring Women's Representation and Independence in Virginia Woolf's A Room of One's Own (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Women have been trying to achieve independence over the centuries. But the things have changed in modern era. Now the women have become more aware about their freedom and identity. Virginia Woolf’s famous essay A Room of One's Own follows the same tradition. A Room of One's Own is actually two lectures given by Virginia Woolf in October, 1928 at two women’s constituent Colleges of Cambridge University. She later enlarged these two lectures and published them together as a full length essay in September, 1929. It is generally believed that women are considered unequal to men, and that is the reason they have created less important piece of literature than that of men. In order to clear her point, Virginia Woolf presents the example of Judith, a fictional sister of Shakespeare.